Health assessment in nursing - Weber, Janet; Kelley, Jane (Philadelphia, Pennsylvania : Wolters Kluwer Health/Lippincott Williams & Wilkins, 2010)
Now in its fourth edition, 'Health Assessment in Nursing' is a colorful, user-friendly introductory level health assessment text for RN-level students. Targeted to ADN and BSN programs, this text presumes no prior knowledge of health assessment and is accompanied by a lab manual, a handbook, and an interactive CD-ROM
Nursing data collection, documentation, and analysis -- Integrative holistic nursing assessment -- Nursing assessment of physical systems -- Nursing assessment of special groups.
Includes index.
Keywords: DIAGNOSTICS INFIRMIERS